PENGEMBANGAN KURIKULUM SEJARAH KEBUDAYAAN ISLAM (SKI) DI MTSN KOTA BANDA ACEH - Nurmawati; Sri Suyanta; Fadhillah (Jurnal Pendidikan Dasar, 2021)
In a formal educational institution , curriculum is an important point where the curriculum becomes a reference for things that must be achieved in every learning process. The curriculum in Indonesian education often undergoes various kinds of changes and is still centralized in which the Indonesian Education Institute focuses more on developed cities in Indonesia as a benchmark for developing the education curriculum in Indonesia. For Islamic Cultural History subjects, curriculum development is regulated directly by the Indonesian Ministry of Religion, the latest development occurred in 2019, where the KMA 183 and 184 curriculum were available. This curriculum encourages and provides rules on how to innovate in the implementation of the madrasa curriculum and provides a legal umbrella in the development of the distinctiveness of Madrasas, the development of character strengthening, Anti-Corruption Education and the Development of Religious Moderation in Madrasas. This study focuses on the development of the SKI curriculum in MTsN in Banda Aceh, the aim is to see how the implementation of the KMA 183 and 184 curriculum and what obstacles are experienced in implementing the curriculum. The results of the study found that the KMA 183 and 184 curriculum really helped students in understanding the material being taught, but some teachers still felt the need for guidance from a competent facilitator in order to be able to apply this curriculum optimally. The main obstacle felt was the lack of procurement of SKI books in accordance with the KMA 183 and 184 curriculum, so that many students did not have these books.